Do Improvements in the Information Environment Enhance Insiders’ Ability to Learn from Outsiders? - LOUREIRO, GILBERTO; TABOADA, ALVARO G. (Journal of Accounting Research, 2015)
ABSTRACT We examine whether and how an exogenous shock to the information environment changes insiders’ ability to learn from outsiders. We document three main findings. First, we find an increase in investment‐to‐price sensitivity following the adoption of International Financial Reporting Standards (IFRS). Second, we show that the relation between the market reaction to M&A deal announcements and the likelihood of deal completion becomes stronger after IFRS adoption. Third, we find significant improvements in post‐acquisition operating and stock return performance post‐IFRS adoption. These results are more pronounced for firms that experienced significant increases in foreign institutional ownership around IFRS adoption, especially when these foreign investors are from countries that matter for the firm’s growth opportunities. Taken together, our findings suggest that insiders’ ability to learn from outsiders improves post‐IFRS, and this improved ability to learn from outsiders leads to real economic gains.